PENEGAKAN HUKUM TINDAK PIDANA KORUPSI YANG BERUPA PENERIMAAN GRATIFIKASI SEBAGAI SUAP - Sunarto Sunarto (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2017)
The phenomenon of gratification today is so endemic and leads to pathological symptoms, which is a condition in which corruption and gratification have been regarded as "limbs" and are no longer unlawful acts, because in addition to being done independently, corruption and gratification are often done in congregation. Whereas normatively, the regulation on corruption and gratification has been regulated in Law Number 20 Year 2001 concerning the Eradication of Corruption. From the surgical case that has been done can be explained that the increasingly rampant gratification of criminal settings in this country is set in Law No. 20 of 2001 on Corruption Eradication with the threat and maximum penalty of life and penalty of 1 billion rupiah, still less serious, less factual, and still limitative in nature, where the requirement for maximum sanction on the perpetrators of gratification crime proven by the court is considered difficult to be fulfilled, because it is based only on the condition of the occurrence of a momentum. From the Supreme Court's ruling it can also be drawn the understanding that the enactment of a life sentence against drug offenders is included because the crime has serious implications for the sustainability of life in society, so that if corruption is based on the same thing,similar to other special crimes. Law enforcement on bribery and gratification in Indonesia is relatively low, although Indonesia has had anti-gratification enforcement devices. However, the implementation of this regulation will still face several obstacles in terms of regulation, enforcement, and community perspective on money laundering crime. When viewed from the point of substance there is still a gap